The Invisible Hand of Planning : Capitalism, Social Science, and the State in the 1920s. - Alchon, Guy, 1951- (Princeton legacy library., 2014)
Guy Alchon examines the mutually supportive efforts of social scientists, business managers, and government officials to create America's first peacetime system of macroeconomic management. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Libra.